Safety evaluation of the food enzyme β‐amylase from genetically modified Bacillus licheniformis strain NZYM‐JA. (18th August 2017) - ,; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Cravedi, Jean‐Pierre; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; Kärenlampi, Sirpa; Mennes, Wim; et al.
Abstract: The food enzyme considered in this opinion is a β‐amylase (4‐α‐d ‐glucan maltohydrolase; EC 3.2.1.2), produced with genetically modified Bacillus licheniformis strain NZYM‐JA by Novozymes A/S (Denmark). The β‐amylase food enzyme is intended to be used in starch processing for the production of glucose syrups. Since the residual amounts of total organic solids (TOS) in glucose syrups after filtration and purification during starch processing were considered negligible, no dietary exposure was calculated. Toxicological tests made with the food enzyme under application indicated that there was no concern with respect to genotoxicity, mutagenicity or systemic toxicity. The allergenicity was evaluated by searching for similarity of the amino acid sequence to those of known allergens; no match was found. The Panel considers that there are no indications for allergic reactions. Based on the genetic modifications performed, the manufacturing process, the compositional and biochemical data provided, the findings in the toxicological studies and allergenicity assessment, the Panel concludes that this food enzyme does not give rise to safety concerns under the intended conditions of use.